La Guera civil española en la revista Sur - Macciuci, Marta Raquel (Centro de Investigaciones Socio Históricas. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2004)
This paper watches in Sur numbers of 1936-1939 the ways of Civil War representations. Victoria Ocampo and the Grupo Sur advocated the republic legality, so these give us a new point of view to research the distance between no-politicize expressions of the institution and its concrete actions. In addition to this and in the same way, it brings to light a new vision of the debated limited interpretations of Sur ideology.